Prostate cancer burden in South Asia: A systematic analysis of global burden of disease data (1990–2021) - Vijay Kumar (377076) (2024)
Objectives The objectives of this study were to analyze trends in prostate cancer incidence, incidence, mortality, and disability‐adjusted life years (DALYs) from 1990 to 2021 via data from the Global Burden of Disease (GBD) study in South Asia. Additionally, the study projects future prostate cancer incidence rates up to 2031 to inform public health interventions in South Asia. Methods Data covering South Asian countries such as Bangladesh, Bhutan, India, Nepal, and Pakistan were obtained from the GBD 2021 portal. Age‐standardized rates (ASRs) for prostate cancer metrics, including incidence (ASIR), prevalence (ASPR), mortality (ASMR), and DALYs (ASDR), were analyzed via joinpoint and ARIMA modeling techniques. Geographic variations in ASRs were mapped via QGIS software. Results The prostate cancer ASIR, ASPR, and ASDR significantly increased from 1990 to 2021, particularly among individuals aged 60–65 years. The highest incidence and mortality rates were observed in Pakistan. The total percentage change in incidence in India was the highest at 61%. Projections indicate a continued rise in prostate cancer incidence, with South Asia's ASIR expected to reach 9.34 per 100 000 by 2031. Conclusions The growing burden of prostate cancer in South Asia highlights the need for enhanced screening programs, public awareness, and healthcare infrastructure improvements. Without intervention, the increasing incidence and mortality rates could strain healthcare resources, emphasizing the urgency of region‐specific public health strategies. Other Information Published in: International Journal of Urology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/iju.15641